American roulette : the social logic of death penalty sentencing trials - Kaufman, Sarah Beth (University of California Press, 2020)
"As the death penalty clings stubbornly to life in many states and dies off in others, this first-of-its kind ethnography of capital trials offers a fresh analysis of the inner workings of American death penalty. Sarah Beth Kaufman draws on years of ethnographic and documentary research, including hundreds of hours of courtroom observation in seven states, interviews with prosecutors, and analyses of newspaper coverage of death penalty cases. Her research exposes the logic of a system that is not explained by morality or justice and does not make sense fiscally, emotionally, or as a crime-control strategy, but instead depends on a series of social logics that go beyond the previously acknowledged problems with race and class discrimination. Taking readers inside capital courtrooms across the country, American Roulette contends that the ideals of criminal punishment have been replaced by logics of performance and politics. The result is a network that assembles the power to decide between life and death, all while suggesting that jurors take ultimate responsibility"--